Mothers' Perceptions of Breastfeeding Success in Coastal Areas: A Review - Listy Handayani; Arni Evayanti; Andi Rini Indriani Saedah (Journal of Health Science and Pharmacy, 2025)
Background: Exclusive breastfeeding during the first six months of an infant's life is strongly recommended by both the World Health Organization (WHO) and the Ministry of Health of the Republic of Indonesia. Breast milk not only provides optimal nutrition but also protects infants from a range of infectious diseases. However, in coastal areas, the practice of exclusive breastfeeding faces more complex challenges. Factors such as maternal knowledge, socio-cultural norms, access to healthcare services, and family support can significantly influence a mother's perception and ability to successfully practice exclusive breastfeeding. Objective: This study aims to analyze the various factors that influence mothers' perceptions of the success of exclusive breastfeeding in coastal communities. Method: This study utilized a literature review approach, drawing upon findings from both national and international journals published within the last six years. A total of 20 relevant journal articles were reviewed, consisting of 13 national and 7 international publications. Article searches were conducted using platforms such as Google Scholar, Mendeley.com, PubMed, and ScienceDirect, covering the publication years from 2018 to 2024. Results: The literature review indicates that factors such as maternal knowledge, family support, cultural practices, and access to health services play a significant role in influencing the success of exclusive breastfeeding in coastal areas. Conclusion: The success of exclusive breastfeeding in coastal areas is greatly influenced by both internal factors such as maternal awareness and external factors, including family and community support. Therefore, community-based interventions and supportive health policies are essential to enhance exclusive breastfeeding practices in these regions. Keywords: Mother’s Perception, Exclusive Breastfeeding, Coastal Areas